2002
DOI: 10.1073/pnas.022618799
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent plasticity without long-term depression by type 2 metabotropic glutamate receptors in developing visual cortex

Abstract: Synaptic depression is thought to underlie the loss of cortical responsiveness to an eye deprived of vision. Here, we establish a fundamental role for type 2 metabotropic glutamate receptors (mGluR2) in long-term depression (LTD) of synaptic transmission within primary visual cortex. Direct mGluR2 activation by (2S,2R,3R-2-(2,3-dicarboxycyclopropyl)glycine (DCG-IV) persistently depressed layer 2͞3 field potentials in slices of mouse binocular zone when stimulated concomitantly. Chemical LTD was independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…However, the role of type II mGluRs in visual cortical LTD remains unclear. In one study, the potent antagonist LY341495 was found ineffective in preventing LTD (Sawtell et al, 1999), whereas a complete block of LTD with the antagonist MCCG was reported recently (Renger et al, 2002). We examined the effects of 10 M MCCG (to selectively block type II mGluRs) and 100 M LY341495 (to block both, type I and type II mGluRs) on LTD under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of type II mGluRs in visual cortical LTD remains unclear. In one study, the potent antagonist LY341495 was found ineffective in preventing LTD (Sawtell et al, 1999), whereas a complete block of LTD with the antagonist MCCG was reported recently (Renger et al, 2002). We examined the effects of 10 M MCCG (to selectively block type II mGluRs) and 100 M LY341495 (to block both, type I and type II mGluRs) on LTD under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3A; ref. 15), suggesting that alternative mechanisms for disconnecting deprived eye input may be involved in a modest role, if at all (28).…”
Section: Discussionmentioning
confidence: 99%
“…As Daw et al (29) have pointed out, closer attention to laminar differences in LTD and ocular dominance plasticity may help resolve some of the lingering controversies in the field (see, e.g., ref. 30).…”
Section: Discussionmentioning
confidence: 99%